Leadership Style and Compensation on Employee Performance at “Simple Fit” Convection Blitar - Nurul Farida; Santi Widyanigryum; Heri Pratikto; Agung Winarno (PT FORMOSA CENDEKIA GLOBAL, 2024)
Using a quantitative technique, this study seeks to ascertain the extent to which employee performance at Konveksi Simple Fit, Blitar Regency is impacted by leadership style and salary. Multiple Linear Analysis Test, The data in this study was analyzed using the following steps: Validity Test, Reliability Test, Normality Test, Partial Test (t Test), Simultaneous Test (F Test), and Determination Coefficient Test (R2). The results of the study showed that: (1) the leadership style variable has a significant effect on the employee performance variable (4.311 with a value of 0.000 less than 0.05); (2) the compensation variable has a significant effect (3.128 with a value of 0.003 less than 0.05); and (3) concurrently Leadership style and compensation are important considerations. 110.055 in the employee performance variable. Employee performance is 83% impacted by leadership style and pay, according to the determination test findings